PENGARUH KECUKUPAN MODAL, PEMBIAYAAN BERMASALAH, BAGI HASIL DAN TINGKAT INFLASI TERHADAP DEPOSITO MUDHARABAH PADA BANK UMUM SYARIAH - Wilda Nurhidayah; Amaliyah Amaliyah (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
This study aims to determine the effect of capital adequacy, problematic financing, profit sharing and inflation rates on Mudharabah deposits in Islamic commercial banks. There are 5 samples in this study that meet the criteria, namely Bank Jabar Banten Syariah, Panin Dubai Syariah Bank, Bukopin Syariah Bank, BCA Syariah and Maybank Syariah Indonesia. The analytical tool used is panel data regression analysis. The chosen model is Random Effect which is tested by F test and t test, with a significance level of 5%. From the results of the analysis, it is known that simultaneous Capital Adequacy, Problem Financing, Profit Sharing and Inflation Rate have a significant effect on Mudharabah Deposits. Partially Capital Adequacy, Problem Financing and Inflation Rate have no significant effect on Mudharabah Deposits while Profit Sharing has a positive and significant effect on Mudharabah Deposits.